Effect of Concrete Properties and Prestressing Steel Reinforcement Type on the Development Length in Pretensioned Concrete Railroad ties - Momeni, Amir F.; Peterman, Robert J.; Beck, B. Terry; Wu, Chih-Hang (Rural Railroad Safety Center, Kansas State University., 2021)
A study was conducted to determine the effect of different concrete properties and prestressing steel reinforcement type on the development length and flexural capacity of prestressed concrete railroad ties. Thirteen different 5.32-mm-diameter prestressing wires and six different strands (four 7-wire strands and two 3-wire strands) were used to fabricate 4-tendon pretensioned prisms with a square cross section. A consistent concrete mixture utilizing Type III cement and a water-to-cementitious ratio of 0.32 was used for all prisms. The prisms were detensioned at concrete compressive strengths of 3500 psi, 4500 psi, and 6000 psi. Load tests revealed that there is a large difference in the development length for different wire/strand types as well as with different concrete release strengths. Additionally, cyclic load tests revealed that there is also a significant difference in the bond performance of these reinforcement types under repeated loadings.
Keywords: Development Length; Wire Bond; Strand Bond; Infrastructure; Railroad Ties; Prestressed Concrete